Español - Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1986)
An approximation to evaluate the pKa values of aminotricarboxylic acids is proposed. By least square treatements, the values of pKa, pK1 and pK2 are obtained; then, pK3 is found by algebraic calculations. The evaluations of pKa of nitrilotripropionic acid is used to ilustrate the utility of the aboye approximation.